2021
DOI: 10.1039/d1cp00105a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of amyloidogenicity and neurotoxicity of a pro-aggregated tau mutant in the presence of histidine tautomerism via replica-exchange simulation

Abstract: The accumulation of ΔK280 tau mutant resulting in neurotoxic oligomeric aggregates is an important but yet mysterious procedure in Alzheimer’s disease (AD) development. Recently, we proposed a histidine tautomerization hypothesis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Previous research , has reported that there are two isomers for His, as depicted in Scheme b, N ε H and N δ H tautomers, and their side chain p K a (∼6) is close to the physiological pH. Just because of N ε and N δ atoms being as both hydrogen bond donor and acceptor along with the tautomerization between isomers, His often lies at the heart of active sites of many proteins and plays key roles in many important biochemical processes. …”
Section: Introductionmentioning
confidence: 97%
“…Previous research , has reported that there are two isomers for His, as depicted in Scheme b, N ε H and N δ H tautomers, and their side chain p K a (∼6) is close to the physiological pH. Just because of N ε and N δ atoms being as both hydrogen bond donor and acceptor along with the tautomerization between isomers, His often lies at the heart of active sites of many proteins and plays key roles in many important biochemical processes. …”
Section: Introductionmentioning
confidence: 97%
“…However, we examined these inter-residue contacts on the basis of the peptide main-chain (MC). The MC contour mapping of a macromolecule has been frequently utilized as a depiction of peptide secondary structure, an essential element in self-assembly and folding phenomena. , Figure exhibits a contact plot for the probability of inter-residual interactions at 308.09 K acquired from the last 100 ns of REMD trajectory analysis with less than 1.5 nm minimum distance between atoms. From the MC–MC contour map, thick bands along the main diagonal adjacent to residues D20–N29 were noticed in the δε and δδ isomers, which indicates a significant presence of α-helices near that region.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of PrP C into PrP Sc and its accumulation are largely dependent on several factors, including amino acid composition, pH, temperature, salt concentration, and the presence of lipids and metal ions. Another aspect that may have an important effect is histidine (His) tautomerization, which has been shown to play a key role in peptide aggregation. Diverse forms of His residues (namely, neutral and protonated) are correlated with organizational properties of different misfolded systems and can influence the accumulation pathways in peptides, leading to proteopathies. However, the intrinsic origin of PrP self-assembly due to diverse His behaviors remains largely undetermined. As misfolding of monomeric PrP and consequent oligomerization/fibrilization are closely connected to prion disease pathology, it is essential to examine the misfolding mechanism of the PrP monomer in the presence of His tautomerism .…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, a novel histidine tautomerism/protonation hypothesis accounting for the pathogenesis of AD and other neurological diseases has been suggested by our research team. 11–26 We have demonstrated that different protonated states in the histidine imidazole ring are related to the conformational characteristics of diverse misfolded peptides (namely Aβ, tau, amylin, and prion) and can influence fibrillization processes in polypeptides, resulting in proteopathies. This histidine hypothesis implies that protein accumulation may occur inherently rather than as a consequence of extrinsic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy has been widely used for studying diverse tautomeric/protonated states of histidines. However, the 15 N and 13 C chemical shifts of histidine are very sensitive to its protonated condition, and the peptide backbone conformation, hence it is not straightforward to characterize the spectroscopic signatures of histidine under different tautomeric/protonated states. Furthermore, the tautomeric equilibration of histidine occurs on the picosecond time scale, limiting use of NMR techniques for real-time monitoring of dimerization upon tautomerization/protonation of histidine moieties.…”
Section: Introductionmentioning
confidence: 99%